2013
DOI: 10.1177/1740774512468806
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of adaptive design variations on the sequential parallel comparison design for clinical trials

Abstract: Background Currently, a growing placebo response rate has been observed in clinical trials for antidepressant drugs, a phenomenon that has made it increasingly difficult to demonstrate efficacy. The sequential parallel comparison design (SPCD) is a clinical trial design that was proposed to address this issue. The SPCD theoretically has the potential to reduce the sample size requirement for a clinical trial and to simultaneously enrich the study population to be less responsive to the placebo. Purpose Becau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…A number of possible contributing factors have been identified, but further studies are needed. The sequential parallel comparison design has been proposed to address this issue and its ability to minimize the placebo effect has been demonstrated [35][36][37]. Statistical modeling has demonstrated that sequential parallel design reduces sample size by 20 --25% relative to traditional parallel design, while retaining similar power, leading to financial savings and shortening total study length by reducing the enrollment period [35][36][37].…”
Section: Methodological Issues In Clinical Trials With Antidepressantsmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of possible contributing factors have been identified, but further studies are needed. The sequential parallel comparison design has been proposed to address this issue and its ability to minimize the placebo effect has been demonstrated [35][36][37]. Statistical modeling has demonstrated that sequential parallel design reduces sample size by 20 --25% relative to traditional parallel design, while retaining similar power, leading to financial savings and shortening total study length by reducing the enrollment period [35][36][37].…”
Section: Methodological Issues In Clinical Trials With Antidepressantsmentioning
confidence: 99%
“…The sequential parallel comparison design has been proposed to address this issue and its ability to minimize the placebo effect has been demonstrated [35][36][37]. Statistical modeling has demonstrated that sequential parallel design reduces sample size by 20 --25% relative to traditional parallel design, while retaining similar power, leading to financial savings and shortening total study length by reducing the enrollment period [35][36][37]. Adaptive design (e.g., treatment algorithms) and equipoise-stratified design (e.g., flexibility in randomization by allowing participants and investigators to choose among groups) will also improve design issues [35][36][37].…”
Section: Methodological Issues In Clinical Trials With Antidepressantsmentioning
confidence: 99%
“…An adaptive design is defined as a clinical trial design that uses accumulating data to decide on how to modify trial and/or statistical aspects of the study as it continues, without undermining the validity and integrity of the trial (30,31).…”
Section: Using Adaptive Design To Calculate Correlation Of Multiple Pmentioning
confidence: 99%